IMPROVING FARMER FINANCIAL MANAGEMENT AND EMPOWERMENT TO BECOME INDEPENDENT FARMERS FOR POVERTY ERADICATION IN GAMPONG MEUNASAH KRUENG VILLAGE, PEUDADA DISTRICT, BIREUEN REGENCY - Sri Yanna; Naziratil Husna; Mirza; Mai Simahatie; Sarah Nadia; Selpi Tiara (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This community service program aims to empower Farmer Groups in Meunasah Krueng Village, Peudada District, Bireuen Regency, through training and assistance in increasing agricultural productivity and strengthening farmers' financial management. The main problems faced by partners are low rice production, weak managerial skills, and dependence on middlemen. The implementation method includes socialization, training (technical guidance), application of appropriate technology, mentoring, and evaluation. The results of the activity showed an increase in rice productivity from 3.5 tons to 6.8 tons per hectare, an increase in financial recording capabilities, and the independence of farmers in business planning. This program supports the achievement of SDGs number 1 (No Poverty), 2 (No Hunger), 8 (Decent Work and Economic Growth), and 12 (Responsible Consumption and Production).